Diphtheria toxin: nucleotide binding and toxin heterogeneity. - Lory, S (1980)
We have used flow dialysis to demonstrate binding of ATP and related compounds to diphtheria toxin. The results define a new site on the toxin molecule (the P site), which has distinctly different properties from the NAD+-binding site of the fragment A moiety. The relative affinities of various compounds for the P site are similar to their capacities to inhibit toxin attachment to cell surfaces and its action on cells. This suggests that the P site may correspond to the binding site for cell surface receptors. Affinity of nucleotides for the toxin depends strongly on the number of phosphates, although both nucleoside and phosphate moieties contribute to the interaction. A substantial fraction of the toxin in any given preparation did not bind ATP in a rapidly reversible manner and was not retained on ATP-Sepharose. This fraction, which varied in magnitude from preparation to preparation, was isolated and shown to contain an endogenous, firmly bound nucleotide or nucleotide-like compound. The presence of this compound may explain some of the physical heterogeneity within individual preparations of purified toxin as well as variations in physical and biological properties among various preparations.